Design of a radial vanadium redox microfluidic fuel cell: A new way to break the size limitation. (4th March 2019) - Li, Li; Bei, Shaoyi; Liu, Ranran; Xu, Qiang; Zheng, Keqing; She, Yiyi; He, Yun
Summary: Microfluidic fuel cell (MFC) suffers from small single cell output power due to the inherent cell size limitation as microscale geometries are prerequisite to prevent reactant crossover between the anode and cathode. To meet the power demand of practical applications, previous works mainly focus on the creating of MFC stacks with multiple cells connected in series, parallel, or mixture of both series and parallel to increase the output power. Yet, low energy efficiency is observed because of the flow distribution nonuniformity and shunt current losses. In this work, a high performance radial vanadium redox MFC is presented to address the size limitation issue by adding a separate layer between the porous electrodes of the conventional plate‐frame MFC. Specific cell characteristics are detailed by mathematical modeling, and parametric studies are performed to evaluate the influences of the geometrical and operational parameters on the cell performance. The results show that this new radial MFC can provide a higher fuel utilization and meanwhile an improved cell performance under a fixed electrode size compared with the conventional plate‐frame MFC. Moreover, the electrode size limitation due to the reactant crossover between the anode and cathode is broken as the influences of the electrode size on the mixing region are greatly reduced. In the case with the electrode size equal to 18 mm × 18 mm, single cell output power of 0.35 mW with a fuel utilization of 53.33% is obtained under the reactant concentration of 2 mol L −1 and flow rate of 300 μL min −1 . Abstract : A radial geometry is introduced into the conventional plate‐frame microfluidic fuel cell. Specific cell characteristics are detailed by mathematical modeling. Inherent size limitation brought by the mixing region is broken by restricting the laminar interface to the electrode edge.